In-situ observation of end crater crack mechanisms in AA7075 during laser beam welding using synchrotron radiation - Forster, Carola; Döring, Markus; Spurk, Christoph; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Schmidt, Michael (Procedia CIRP, 2024)
AA7075 is increasingly used in the aerospace industry due to its excellent strength to weight ratio. However, due to an extended solidification interval of its alloy components magnesium, zinc and copper, it is highly susceptible to solidification cracking and thus has limited suitability for laser beam welding processing. The formation of end crater cracks is a particular challenge. This study investigates the formation and propagation of cracks in AA7075 during laser beam welding at different beam diameters, feed rates and laser powers by using an in-situ X-ray high-speed imaging technique utilizing synchrotron radiation. The experiments were conducted at the German Electron-Synchrotron (DESY) at Petra III, beamline P07. The results show a correlation between cumulative crack length, solidification rate and energy input, providing important insights to improve the weldability of AA7075.
CRIS-Team Scopus Importer:2024-09-27
Keywords: AA7075; End crater cracks; Laser beam welding; Solidification cracks; X-ray imaging